Effectiveness of transcranial alternating current stimulation (tACS) and cognitive bias modification (CBM) in treating anxiety, depression, attentional bias, and drug craving in opioid-dependent patients - Kiyanoosh Papi; Masoud Nosratabadi; Farhad Taremian; Nikzad Ghanbari; Maryam Ebrahimi Varkiyani (Acta Psychologica)
Introduction: Substance Use Disorders (SUDs) pose significant challenges globally, with opiate addiction being particularly prevalent. This study investigates the impact of transcranial alternating current stimulation (tACS) at 10 Hz and individual alpha frequencies (IAF), along with cognitive bias modification (CBM), on drug craving, anxiety, depression, and attention bias in individuals with SUDs. Methods: Participants (N = 72) were allocated to control, tACS 10 Hz, tACS IAF, Sham, CBM, and CBM + tACS groups (n = 12 each). Measures included demographic questionnaires, dot probe tasks, Desires for Drug Questionnaires (DDQ), DASS-21 assessments, and Visual Analog Scale (VAS) for craving. Mixed repeated measures ANOVA were conducted, revealing significant interactions (TIME*GROUP), indicating differential treatment effects over time. Findings: The study involved 72 substance abusers divided into six groups: control, tACS.10 Hz, tACS Real, Sham, CBM, and CBM + tACS. Demographic variables were similar among groups. Mixed ANOVA showed significant TIME*GROUP interactions for all assessments. Significant differences were found in anxiety, drug dependence, and visual analog scale measures. Conclusion: In brief, although using tACS and CBM separately didn't lead to significant decreases in substance-related issues, employing them together demonstrated potential. This research underscores how the brain can adapt to electrical stimulation and emphasizes the importance of delving deeper into treating SUDs. However, limitations such as limited participant availability and the reliance on verbal craving induction indicate the necessity for more comprehensive study designs and varied assessment methods in future investigations.